THE STUDY ONTHE IMPLEMENTATION OF BASIC AUTOMOTIVE ENGINEERING LEARNING - Wuskha, Zainul; Rohendi, Dedi; Muhammad Noor, Ridwan Adam (Journal of Mechanical Engineering Education, 2020)
This research aims to describe the implementation of learning from various learning activities and know the response of students. Based on the observation results of anumber of students in automotive basic engineering subjects at Bandung Vocational High School 6the study results are still not in line with expectations. The research method used is quantitative descriptive. The population of this study is the teacher ofautomotive basic engineering subjects and all students of grade X TKRO. A sample of 63 students used the study. Research data is obtained with observation sheets to observe the implementation of learning and polls are disseminated by utilizing google forms to obtain student responses. The results of the assessment of learning experts state that research instruments are valid for use. The results of the data analysis show the implementation of automotive basic engineering learning starting from preliminary activities, core activities and closing activities get good category. The conclusion of this study is that the implementation of automotive basic engineering studies in Bandung Vocational High School 6has been well underway in accordance with the provisions set out. Grade X TKRO students gave a positive response to the implementation of automotive basic engineering learning.